(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine The Simple model for Newton’s II Law and its application. The sample of this study is 20 sample variation. Data analysis technique used is by regression analysis. From the results of the analysis it was found that Freghitung=4,28 and Freg-table =4,13 (Freg-count >Freg-table), so the conclusion of this study is that there is a very large the simple model of Newton’s II law and its application.